Encontrando mi espacio: desplazamiento y vivencias de las mujeres de los sectores urbano-populares de San José, Costa Rica (1950-1980) - Ramírez Achoy, Jéssica (Revista de historia., 2013)
The paper analyzes the issue of women’s mobilization in historical perspective, for that, the subject is contextualized with the main events of Costa Rica and the construction of the neighborhoods in South of San José. We discuss the women’s role based on political and economic changes, as well as, the use that they gave the public space or the communities located in the southern suburbs of San José.